2003
DOI: 10.1063/1.1581986
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional periodic positioning of self-assembled Ge islands on prepatterned Si (001) substrates

Abstract: Two-dimensional (2D) periodic arrays of Ge islands were realized on prepatterned Si (001) substrates by solid-source molecular-beam epitaxy. Atomic-force microscopy images demonstrate that the Ge islands are formed in the 2D laterally ordered pits of patterned substrates. The 2D periodicity of the substrate pattern is replicated throughout a stack of Ge island layers by strain-driven vertical ordering. Photoluminescence spectra of the ordered Ge islands show well-resolved peaks of the no-phonon signal and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 13 publications
1
99
0
Order By: Relevance
“…Consequently, some years ago a templated selfassembly of semiconductor nanostructures was introduced, [30][31][32][33][34][35][36][37] combining growth on patterned substrates for the definition of an initial two-dimensionally periodic island layer with subsequent vertical ordering due to the strain fields of the buried quantum dots in a multidot layer system. 38,39 So far, in particular, three-dimensionally ordered structures of InAs/GaAs ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, some years ago a templated selfassembly of semiconductor nanostructures was introduced, [30][31][32][33][34][35][36][37] combining growth on patterned substrates for the definition of an initial two-dimensionally periodic island layer with subsequent vertical ordering due to the strain fields of the buried quantum dots in a multidot layer system. 38,39 So far, in particular, three-dimensionally ordered structures of InAs/GaAs ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Lithographic techniques are best suited for the fabrication of a two-dimensional ͑2D͒ patterned Si template with sufficient perfection in periodicity and size of the predefined nucleation sites for the dots. For this purpose, electron-beam ͑e-beam͒ lithography, 32 optical interference lithography, 33 and ion-beam lithography 34,35 have been used to fabricate prepatterned Si substrates. Whereas the first two approaches write the pattern for the nucleation site for each individual dot sequentially, the optical interference technique allows the prepatterning of large 2D arrays in a single exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments (e.g. [223]) have demonstrated that both positional order and size uniformity can be obtained (see Figure 8(a)), provided that suitable growth conditions are matched [226]. Simulations studying the island growth on wavypatterned substrates have been reported in Refs.…”
Section: Substrate Patterningmentioning
confidence: 99%
“…The patterning of the substrate is a well-established method to direct and control the growth of islands into ordered arrays, with improved shape and size homogeneity [221][222][223][224]. From the point of view of the modelling, the effect of patterning turns into a modulation of the chemical potential.…”
Section: Substrate Patterningmentioning
confidence: 99%
“…Today several techniques are used to obtain ordered arrays of Ge(Si) nanoislands. In recent years, to organize arrays of Ge(Si) islands, they use their growth on an undulating surface formed by deposition of , containing a grid of misfit dislocations [5], the growth in pre-structured Si substrates [6]. Application of these techniques allows obtaining the ordered chains of nanoislands with a high linear density, but in this case their two-dimensional density still remains low.…”
Section: Introductionmentioning
confidence: 99%